Making their own weather? - Martins, Pedro S. (2023)
Funding Information: The authors thank the Editor, three referees, Orley C. Ashenfelter, Andrea Bassanini, Eve Caroli, Wenjing Duan, Judite Goncalves, Juan Jimeno, Claudio Lucifora, Ioana Marinescu, Evan Starr, Marshall Steinbaum, Bledi Taska and conference/workshop participants at the American Economic Association (San Diego), Queen Mary University of London, and the European Commission for comments. The authors also thank INE and the Ministries of Education and Employment, Portugal, for data access, the European Union for financial support ( VS/2016/0340 and VP/2019/004/0038 grants) and Joana Saraiva for research assistance. António Melo acknowledges funding by a Ph.D. scholarship from Fundação para a Ciência e Tecnologia ( SFRH/BD/146123/2019 ). The usual disclaimer applies. Funding Information: The authors thank the Editor, three referees, Orley C. Ashenfelter, Andrea Bassanini, Eve Caroli, Wenjing Duan, Judite Goncalves, Juan Jimeno, Claudio Lucifora, Ioana Marinescu, Evan Starr, Marshall Steinbaum, Bledi Taska and conference/workshop participants at the American Economic Association (San Diego), Queen Mary University of London, and the European Commission for comments. The authors also thank INE and the Ministries of Education and Employment, Portugal, for data access, the European Union for financial support (VS/2016/0340 and VP/2019/004/0038 grants) and Joana Saraiva for research assistance. António Melo acknowledges funding by a Ph.D. scholarship from Fundação para a Ciência e Tecnologia (SFRH/BD/146123/2019). The usual disclaimer applies. Publisher Copyright: © 2023 The Author(s)